End-of-injection fuel dribble of multi-hole diesel injector: Comprehensive investigation of phenomenon and discussion on control strategy. (1st October 2016) - Moon, Seoksu; Huang, Weidi; Li, Zhilong; Wang, Jin
Highlights: End-of-injection fuel dribble of multi-hole diesel injector is investigated. High-speed X-ray phase-contrast imaging technique is employed for flow analysis. In-nozzle bubble formation and air ingestion are promoted at high injection pressures. Needle closing speed is the primary factor governing the fuel dribbling process. Control strategies of fuel dribble from modern diesel injectors are discussed. Abstract: The needle shutdown of fuel injectors leads to an undesired fuel dribble that forms unburned hydrocarbons and decreases the engine thermal efficiency in modern engines. Understanding of the fuel dribbling process is of great importance to establish its minimization strategy for optimal use of conventional fuels. However, the detailed needle dynamics and in- and near-nozzle flow characteristics governing the fuel dribble process have not been thoroughly understood. In this study, the needle dynamics, in- and near-nozzle flow characteristics and fuel dribble of a mini-sac type three-hole diesel injector were investigated using a high-speed X-ray phase-contrast imaging technique at different injection pressures. The results showed that an increase in injection pressure increased the flow evacuation velocity at the needle close that induced a more intense fuel cavitation and air ingestion inside the nozzle. The fuel dribbling process showed a high shot-to-shot deviation. A statistical analysis of 50-shot results exhibited two breakup modes of fuel dribble determined by the flow evacuation velocity at the needle close and presence of air ingestion. In the first mode, the fast breakup with a short residence time of fuel dribble occurred. Meanwhile, the dripping of undisturbed liquid column with a long residence time of fuel dribble occurred in the second mode. An increase in injection pressure increased the population of the first mode due to more intense air ingestion that primarily caused by an increase in needle closing speed other than an increase in peak injection velocity. Based on the results, the formation mechanism and control strategies of the fuel dribble from modern diesel injectors were discussed.